A method of economic analysis and cost assessment for the installation of marine stream turbines. - Giachero, Guilherme de Faria (2022)
Efficient energy generation is a pressing challenge inherent to human activity and development. From the installation of industries on the riverside to the expansion of nuclear technology, humanity must be prepared for the increasing demand of the next 20 years, with intense electrification and reduction of fossil fuels. By then, it is expected that the demand for electricity doubles. Climate change due to the emission of greenhouse gases put tight constraints on our use and generation of electricity. In this scenario, accounting for environmental problems and market issues, a change in the conventional energy matrix is inevitable, creating space for the use of other sources, especially renewables. This master\'s thesis addresses research on conversion of marine current energy to supply electricity proposing a methodology for economic feasibility analysis. In the first part of this work, a literature review is presented, delineating current endeavors regarding stream energy harnessing. In the second part, a methodology is presented to assess the cost and power generation capability of a generic tidal farm. In the third part, a business case using real-world conditions is presented, to test the proposed methodology and to offer results regarding the feasibility of a specific endeavor. Lastly, an analysis of the results is presented, as well as the suggestion for future work in this current field.